(untitled) (Baghdad Science Journal, 2020)
This work describes the enhancement of phenol red decolorization through immobilizing of laccase in chitosan and enzyme recycling. Commercial laccase from white rot fungus, Trametesversicolor (Tvlac), was immobilizedin to freshly prepared chitosan beads by using glutaraldehyde as a cross linker. Characterization of prepared chitosan was confirmed by FTIR and scanning electron microscope (SEM). Tvlac (46.2 U/mL) immobilized into chitosan beads at 0.8 % glutaraldehyde (v/v) within 24 hrs. Synthetic (HBT) and natural (vanillin) mediators were used to enhance dye decolorizoation. It was found that 89 % of phenol red was decolorized by chitosan beads within 180 min. in the absence of enzyme and mediator, while decolorization percentage of the dye was completed (100%) at 120 min. when chitosan immobilizedlaccase was applied. Moreover, the decolorization was completed within 25 and 50 min. in the presence of chitosan immobilized laccase and of HBT or vanillin respectively. On the other hand, the recycling of chitosan immobilized laccase was still decolorize phenol red and continued up to ninth cycle to reach 70% of dye decolorization .